2020
DOI: 10.1177/1042258720929890
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Leaps: Growth Processes in Transition Phases Between Dynamic States

Abstract: We use a multiple case study approach to investigate “entrepreneurial leaps,” transition phases between dynamic states in which entrepreneurial action focused on reconfiguring key elements of the business model allows a firm to tap into new pools of resources through accessing and exploiting new market. Based on an analysis of 24 cases from three European countries, we derive a general process model of entrepreneurial leaps and identify four different patterns of how these transitions typically unfolds. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…It has been shown that the dynamic-states approach is specifically consistent with the BM concept and BMs' non-linear dynamics; hence, dynamic states represent "the best perceived match between a business model and the market potential" (Levie & Lichtenstein, 2010: 333). This is because BMs contain the inherent feature of being both stable and dynamic at the same time, in order to maintain themselves as a whole and remain sustainable and viable in face of external changes (Sternad & Mödritscher, 2022) T A B L E 3 Additional evidence from the data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that the dynamic-states approach is specifically consistent with the BM concept and BMs' non-linear dynamics; hence, dynamic states represent "the best perceived match between a business model and the market potential" (Levie & Lichtenstein, 2010: 333). This is because BMs contain the inherent feature of being both stable and dynamic at the same time, in order to maintain themselves as a whole and remain sustainable and viable in face of external changes (Sternad & Mödritscher, 2022) T A B L E 3 Additional evidence from the data.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this approach crucially reveals BMs as being in “constant flux” (Andries et al, 2013: 308), thereby showing that businesses sustain their existence by continuously redesigning their BMs. In this regard, the dynamic states perspective employed here (Levie & Lichtenstein, 2010; Sternad & Mödritscher, 2022) serves as a fruitful approach to grasp the changes that firms undergo so as to remain viable under adversity, even as they maintain their structure and functioning. We thereby also respond to calls in the literature to examine BM dynamics not only in young ventures but also in established firms (Demil et al, 2015; Schaltegger et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Continued tension and a strong belief that the projection is correct, results in relief of that tension. This relief is not incidental but intentional (Lichtenstein, 2016; Sternad and Mödritscher, 2020) and is achieved by means of the entrepreneur acting on the opportunity. Each phase of opportunity tension, if relieved or acted upon, leads to the generation of value in the form of new products, diversification, a new or modified business model, growth and/or a continued means of survival and thus a new dynamic state.…”
Section: Theorymentioning
confidence: 99%